Power and Caution: The Ethics of Self-Disclosure - Ejsing, Anette (Teaching theology and religion, 2007)
Good teaching is both powerful and cautious. It is powerful insofar as it creates engaged students. Because an engaged mind is particularly receptive, however, good teaching is also cautious insofar as it provides students with focused guidance through the process of appropriating the learning material. This article reflects critically on expressionist pedagogy by evaluating a classroom situation in which students reacted in unexpected ways to the professor's disclosure of a personal story. It concludes that effective teaching exceeds the goal of merely facilitating student engagement. That is, the use of self-disclosure has the power to create engaged students, but it also requires cautious content consideration when facilitating post-disclosure learning. If, by using the powerful expressionist pedagogy of self-disclosure, we engage students but fail to cautiously guide them through the learning material, we have not taken seriously the ethical responsibility that teaching also implies.